Cramér‐Rao lower bound with Pd < 1 for target localisation accuracy in multistatic passive radar. Issue 7 (1st August 2014) - Anastasio, Valeria; Farina, Alfonso; Colone, Fabiola; Lombardo, Pierfrancesco
Abstract : By exploiting the sources of opportunity not designed for radar applications, the passive radar system often operates with a P d in the range from 60 to 85% for acceptable false alarm rates. Multistatic radar networks can be used to both increase detection capability and localisation accuracy. The standard Cramér‐Rao lower bound (CRLB) cannot be used for a realistic assessment of the target localisation accuracy in a surveillance area since it provides optimistic predictions. In this study, the authors derive the CRLB with missing observations, namely for P d < 1, for the multisensory case. The results are illustrated for the case study of a multistatic passive radar exploiting FM radio transmissions where each bistatic pair within the network is assigned with a detection probability for each target position in the surveillance area. The obtained CRLB with P d < 1 is then employed to compare the localisation performance achievable by a multistatic passive radar when using different sets of measurements: (A) only range measurements, (B) range and Doppler frequency measurements and (C) Doppler frequency measurements only. The reported results show that the proposed CRLB with P d < 1 yields a more reliable prediction of the achievable performance thus allowing a fair comparison of the above different strategies for target localisation.